Does Gender Really Matter: Childhood Trauma, Trait Anger, and Suicide Risk in Early Adulthood - Yarar, Esra Zıvralı (Journal of interpersonal violence, 2023)
Background: Previous studies have reported mixed findings regarding gender differences in suicidal behavior. This discrepancy may be partly attributable to common predictors of suicide risk, such as childhood trauma and anger, and may also be independent of gender. Objectives: The present study investigated gender differences in the impact of childhood trauma and current trait anger on suicide risk, in a group of young Turkish adults. We hypothesized that trait anger would mediate the association between childhood trauma and suicide risk, independently of gender. Participants and Setting: Participants were 589 university students (84.3% women) aged 18–34 years (M = 21.43, SD = 1.82). Methods: Gender group differences in suicide risk, history of childhood trauma, and trait anger as well as possible covariates (i.e., self-rated socio-economic status and academic performance) were assessed. Possible predictors of suicide risk in gender groups were examined. The role of trait anger as a mediator of the relationship between childhood trauma and suicide risk was also examined. Results: Results showed that men reported a higher suicide risk, history of childhood trauma, and trait anger than women. Early childhood trauma and current trait anger scores were significant predictors of suicide risk in both gender groups. Trait anger significantly mediated the relationship between early trauma history and risk for suicide, independently of gender. Conclusions: Study findings support early reports of the effects of childhood trauma and trait anger on suicide risk. It was suggested that preventive interventions for suicidal behavior and monitoring risk groups with aggressive tendencies and childhood trauma history may be important.